Scamorza: a cheese for smallholders - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Smallholder milk production has been boosted in the Arusha Kilimanjaro region of Tanzania. With the he of FAO's Rural Dairy Development Training Team, ILCA has been looking at ways for smallholders to produce scamorza, a pasta-filata-type cheese....